Programma ustranenija bolevogo sindroma v spine - Burmistrov, D. A.; Stepanov, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
Having analysed the special literature concerning the question of occurrence of chronic pains in a back, the authors came to the conclusion, that the pain in a back is a result of a muscular spasm which occurrence can be observed at the presence of the osteochondrosis or other disease or a trauma of a backbone, and at their absence.